Sr and Nd isotopes of cold seep carbonates from the northern South China sea as proxies for fluid sources. (May 2020) - Ge, Lu; Chen, Wei; Zhu, Bi; Fan, Meitong; Yang, Tao; Jiang, Shaoyong
Abstract: In this study, Sr isotopes combined with Nd isotopes of modern cold seep carbonates were studied to provide reliable proxies for sources and pathways of seep fluids. We presented Sr and Nd isotopes together with stable carbon and oxygen isotope data of cold seep carbonates recovered from the northern continental slope of the South China Sea (SCS). Based on the evidence for negligible detrital contamination and diagenetic alteration, carbonate samples are considered dependable archives which record Sr and Nd isotope signals of the original pore waters from which carbonates have precipitated. Excellent correlation between 87 Sr/ 86 Sr ratios and 1/Sr observed in carbonate samples indicates two end-members with distinct Sr isotopic signatures, including modern seawater as a major source and a lesser contribution from methane-rich seep fluid driven from a deep source. Besides these two end-members, release of Nd from organic matter and Fe–Mn oxyhydroxide is an additional contribution to pore water Nd. Furthermore, Sr and Nd isotopic compositions suggest water-rock interactions between upward seep fluid and detrital component in sediments, which resulted in the isotopic shift towards pronounced 143 Nd depleted and slightly 87 Sr enriched in the fluid phase. This study provides insight into the knowledge for tracing seepage fluid circulation by Sr–Nd isotope system at modern seep systems. Highlights: Nd isotopes of cold seep carbonates are investigated for the first time in the South China Sea. Sr and Nd isotopic compositions indicate pore waters mixing by multiple end-members. Water-rock interactions between seep fluid and sediments result in the isotopic shift in fluid phase.